The Effect of Text-to-Speech (TTS) as Language Exposure Towards Students' Reading Comprehension - Falwa Dzikri Ekaputra; Rama Dwika Herdiawan; Eka Nurhidayat (Papanda Journal of English Education, 2023)
The role of language exposure on improving learner’s language skills is a known fact, it is proven with many research supported the claim that language exposure is indeed important. It is obvious for EFL learners to have enough reading comprehension skills to help them learn the language such as reading and understanding learning materials, understanding questions in a test, understanding instruction written in their assignment, etc. The problem lies on how EFL learners in Majalengka are conditioned to not have any English language exposure outside English class at school. The aims of this study is to find how English exposure affect the English reading comprehension of EFL learners who live in multilingual environtment with lots of non-English language exposure. The researcher use one group pre-test post-test design. The researcher find that the text-to-speech treatment was indeed showing an effect towards students’ reading comprehension. Text-to-Speech as Language Exposure is indeed has an effect towards Students’ Reading Comprehension. Unfortunately the effect is negative as the mean score between pre-test and post-test decreased by 12 or 26,5%. The researcher believe that language exposure should not affect students negatively at any way therefore the researcher suggest for the next research, students’ motivation, students’ attention span, students’ will, and students’ seriousness should be take acountable, increased, and kept high during the test in which it is crucial to the final results of the research.